A randomised controlled pilot study of Experience Focused Counselling with voice hearers. Issue 1 (2nd January 2017) - Schnackenberg, Joachim; Fleming, Mick; Martin, Colin R.
Abstract : Background: There is a need for improved psychosocial interventions for distressed voice hearers. Aims: To evaluate a novel approach to hearing voices: Experience Focused Counselling (EFC) aka Making Sense of Voices. Study design and methods: Twelve voice hearers were randomly assigned to a 44-week EFC or Treatment As Usual intervention as part of a pilot study design. Results: At the end of intervention, EFC showed clinically large treatment effect improvements on the Brief Psychiatric Rating Scale – Expanded Version psychotic symptoms (Cohen's d =1.6) and overall psychopathology domains ( d =1.3), and the Psychotic Symptom Rating Scales voices ( d =1) and delusions (aka non-shared reality) ( d =1) scales. EFC voice hearers also felt more able to do first trauma disclosures ( n =4) than TAU group voice hearer ( n =1). Discussion: EFC improvements may have been related to the focus on reducing voices-related distress. EFC holds some promise as a safe and effective intervention for voice hearers, with possible improvements in general psychopathology, psychosis, voices and non-shared reality (aka delusions)-related distress. This will need replicating in more powerful studies.